2021
DOI: 10.1016/j.childyouth.2021.106190
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and adolescents’ perceptions of parental involvement and their relationships with depression among Chinese middle school students during the COVID-19 pandemic

Abstract: Although psychological stress that adolescents may encounter during the COVID-19 pandemic has been of increasing interest to scholars, few studies have examined the profound impact that parents give to adolescents when staying indoors. This study surveyed 1,550 students and their parents from eight middle schools in eastern China. We employed multiple linear regressions with school fixed effects to examine the different perceptions of parental involvement between parents and children, and the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 53 publications
(77 reference statements)
1
23
1
Order By: Relevance
“…Consistent with prior research (Paulson, 1994;Paulson and Sputa, 1996;DePlanty et al, 2007;Thomas et al, 2020;Liu et al, 2021), this study revealed that Chinese parents and their children had different perceptions of parental involvement. Some past studies found that parents reported higher levels of parental involvement behaviors than their children (Paulson, 1994;Paulson and Sputa, 1996;DePlanty et al, 2007), while the results showed that parents could either report a higher or a lower level of parental involvement than their children.…”
Section: Discrepancies In Parents' and Adolescents' Perceptions Of Pa...supporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with prior research (Paulson, 1994;Paulson and Sputa, 1996;DePlanty et al, 2007;Thomas et al, 2020;Liu et al, 2021), this study revealed that Chinese parents and their children had different perceptions of parental involvement. Some past studies found that parents reported higher levels of parental involvement behaviors than their children (Paulson, 1994;Paulson and Sputa, 1996;DePlanty et al, 2007), while the results showed that parents could either report a higher or a lower level of parental involvement than their children.…”
Section: Discrepancies In Parents' and Adolescents' Perceptions Of Pa...supporting
confidence: 90%
“…Similarly, although Liu et al (2021) did not examine parental daily involvement, they found that both parents and children reported a higher level of parent-child communication than parental academic involvement. This might result from the relatively less time and energy required by the parental daily involvement than by the other types of parental involvement, especially parental academic involvement.…”
Section: Discrepancies In Parents' and Adolescents' Perceptions Of Pa...mentioning
confidence: 92%
See 1 more Smart Citation
“…Second, we need to understand how parental involvement contributes to students’ learning and socioemotional well-being during the school suspension ( Demir and Demir, 2021 ; Lawrence and Fakuade, 2021 ; Liu et al, 2021 ; Yang et al, 2022 ). The knowledge gleaned from research in this area can inform parental involvement practices in the New Normal of education—situations that call for agile switching across blended, fully online (asynchronous or bichronous), or hybrid (combining face-to-face and online synchronous at the same time) learning modes ( Martin et al, 2020 ; Morse et al, 2022 ), which may be compelled by future episodes of mandatory school suspension or in support of pedagogical innovation initiatives.…”
Section: Introductionmentioning
confidence: 99%
“… Wang et al (2021) found that adolescents who received more parental social support had higher levels of positive affect and lower levels of negative affect in the United States. Liu et al (2021) reported that higher levels of parental academic involvement and lower levels of parent–child communication was associated with higher levels of middle school student depression during the pandemic in China. Yang et al’s (2022) study showed that middle school students in China had higher levels of affective engagement in their learning if they had involved parents and supportive teachers.…”
Section: Introductionmentioning
confidence: 99%